Improving Cycling Behaviors of Dockless Bike-Sharing Users Based on an Extended Theory of Planned Behavior and Credit-Based Supervision Policies in China - Sun, Lanying; Zhou, Xing; Sun, Zhaohui (Frontiers in Psychology, 2019)
Motivating users’ civilized cycling plays a significant role in alleviating the troubles of dockless bike-sharing programs (DBSPs) and promoting the sustainable development of bike-sharing organizations. Based on the theory of planned behavior (TPB) and observed practices in China, this study develops a theoretical framework to examine how attitudes, subjective norms, perceived behavioral control, and personal norms motivate users’ civilized cycling behavior through civilized cycling intentions. Furthermore, the moderating effect of perceived policy effectiveness between users’ civilized cycling intention and their actual behavior is tested. Using structural equation model-multiple group analysis (SEM-MGA) for a sample of 874 valid questionnaire responses in Beijing and Shanghai, China, our results reveal that (1) attitude, perceived behavioral control and personal norms are positively related to both users’ civilized cycling intentions and their actual behavior, while subjective norms positively affect users’ civilized cycling intention only；(2) users’ civilized cycling intentions mediate the relationship between the four influencing factors and their actual behavior; and (3) perceived policy effectiveness plays a moderating role for the effect of users’ civilized cycling intentions on their actual civilized cycling behavior. Our results indicate that the four influencing factors can encourage users’ civilized cycling behavior, especially when civilized cycling intention exists. Policies like credit-based supervision mechanisms could promote users’ civilized-cycling intentions, which could then be transformed into actual behavior.